2020
DOI: 10.3390/coatings10060565
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Energy Density on Interfacial Diffusion Bonding and Surface Density of Chromium Coating by Multi-Arc Ion Plating on Zirconium Alloy

Abstract: The chromium coating prepared by multi-arc ion plating on the surface of zirconium alloy is easy to fall off under extremely harsh conditions due to the defects of larger particles, pores and weak adhesion between the coating and the zirconium alloy substrate. Here we apply a new composite process for the fabrication of Cr coating by laser melting multi-arc ion plating technology. The numerical model of temperature field laser melting treatment was established, and based on the analysis of the above temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The melt pools become stable under a moderate laser power. A further increase in the scanning speed under a low laser power leads to insufficient energy within the melt pools, resulting in the increase of unmelted powder particles and pores, thus exhibiting a decreasing trend of the relative density [ 32 , 33 , 34 ]. As shown in Table 3 , the Pearson correlation analysis was used to analyze the correlation between the energy density, the laser power, and the laser scanning speed via SPSS.…”
Section: Resultsmentioning
confidence: 99%
“…The melt pools become stable under a moderate laser power. A further increase in the scanning speed under a low laser power leads to insufficient energy within the melt pools, resulting in the increase of unmelted powder particles and pores, thus exhibiting a decreasing trend of the relative density [ 32 , 33 , 34 ]. As shown in Table 3 , the Pearson correlation analysis was used to analyze the correlation between the energy density, the laser power, and the laser scanning speed via SPSS.…”
Section: Resultsmentioning
confidence: 99%
“…Laser melting is also a potential method for coating pretreatment, which aims to strengthen the adhesion property and improve the surface density of coatings. For instance, laser melting method is used by Hu et al [108] on multi-arc ion plated Cr coating Zr alloy samples. The authors found that an interface metallurgical bonding is formed when the laser energy density is high enough to heat the sample surface higher than the Cr-Zr eutectic point.…”
Section: Pretreatmentmentioning
confidence: 99%
“…Concerning the coating techniques, laser surface modification, vapor deposition (PVD and CVD), thermal spray, electroless plating, hot isostatic pressing, and microarc oxidation are widely investigated for cladding coatings. [9,[11][12][13][14][15] Electroless plating has become an irreplaceable surface coating technology because of its advantages such as being suitable for various substrates, uniform thickness, no electrical energy required, and favorable coating performance. [16] Electroless nickel plating is the most common electroless plating method.…”
Section: Introductionmentioning
confidence: 99%